Oral Microbiota in Severe Early Childhood Caries in Thai Children and Their Families: A Pilot Study - Ledder, Ruth G.; Kampoo, Kanokporn; Teanpaisan, Rawee; McBain, Andrew J. (Frontiers in Microbiology, 2018)
Thailand has a comparatively high prevalence of severe early childhood caries (SECC). SECC adversely affects the quality of life for children and their caregivers and represents a considerable economic burden. We have assessed the bacteriological composition of unstimulated saliva, dental plaque and degraded dentine in a Thai cohort, including children with SECC and children without active caries; their siblings, and their primary caregivers. Samples were collected during a dental examination and patients were scored for plaque accumulation and their decayed, missing, and filled teeth (DMFT) index. Samples were analyzed using differential bacteriological counting and gel-based eubacterial DNA profiling. Plaque Lactobacillus abundance correlated significantly with SECC. Whilst Lactobacillus counts were significantly higher in children with SECC than in their siblings and primary caregivers (five families), the opposite trend was apparent for caries-free children. Counts of Gram-negative anaerobes were significantly lower in children with SECC than orally healthy children. SECC correlated significantly with plaque index scores, DMFT, and with Lactobacillus abundance in a highly predictive manner. DNA profiles showed significant homology between families but not within or between non-carious and SECC groups. In conclusion, salivary and plaque Lactobacillus counts were significantly associated with SECC in the Thai subjects. Lactobacillus counts in the children were not correlated with those of their siblings and primary caregivers. Individuals could be significantly differentiated based on family but not on caries status.